2011
DOI: 10.1177/1049909111411471
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Activation and Therapeutic Exposure for Bereavement in Older Adults

Abstract: The development and clinical trial of a 5-session behavioral intervention for complicated bereavement (CB) is presented. We conceptualized CB in terms of Major Depression (MDD) and Post-traumatic Stress Disorder (PTSD) and consequently applied treatment components of Behavioral Activation and Therapeutic Exposure (BA-TE). In order to assure standardization of treatment, control costs, and engage patients, a multi-media, multi-context format was adopted to address avoidance and withdrawal behaviors conceptualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 42 publications
3
48
0
1
Order By: Relevance
“…Acierno et al (2012) showed that individuals with varied levels of training and expertise (ranging from recent graduates of bachelor programs in psychology to experienced social workers) were able to implement behavioral activation. Moreover, behavioral activation interventions delivered via telephone Quijano et al, 2007) or videoconferencing (Lazzari et al, 2011) were also effective.…”
Section: Participant and Setting Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Acierno et al (2012) showed that individuals with varied levels of training and expertise (ranging from recent graduates of bachelor programs in psychology to experienced social workers) were able to implement behavioral activation. Moreover, behavioral activation interventions delivered via telephone Quijano et al, 2007) or videoconferencing (Lazzari et al, 2011) were also effective.…”
Section: Participant and Setting Characteristicsmentioning
confidence: 99%
“…Other studies used collaborative activity selection based on individual goal setting (Bottonari et al, 2008;Lazzari et al, 2011;Quijano et al, 2007;Rokke et al, 1999;Snarski et al, 2011;Turner & Leach, 2009;Yon & Scogin, 2009). Scheduled activities based on clientrated levels of difficulty were also used (Acierno et al, 2012;Clignet et al, 2012;Lazzari et al, 2011;Snarski et al, 2011). Acierno et al (2012) incorporated social aspects into selected activities as often as possible, and included identifying activities that were negatively reinforcing (e.g., chores that reduced stress when finished) and activities that were incompatible with avoidance behavior.…”
Section: Intervention Componentsmentioning
confidence: 99%
See 3 more Smart Citations